2023
DOI: 10.3389/fgene.2022.1075617
|View full text |Cite
|
Sign up to set email alerts
|

The role of landscape evolution in the genetic diversification of a stream fish Sarcocheilichthys parvus from Southern China

Abstract: Sarcocheilichthys parvus (Cypriniformes: Gobionidae) is a stream fish which is endemic to sub-tropical coastal drainages in southern China, thus offering a valuable model for understanding how genetic divergence arises in stream-adapting freshwater fishes in this region. Using the mitochondrial Cyt b gene, integrative analyses of phylogeny, population demography, and ancestral area and paleo-drainage reconstructions are carried out to explicitly explore the role of landscape evolution in genetic diversificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 86 publications
(108 reference statements)
1
1
0
Order By: Relevance
“…As a small resident stream fish, the pale chub might be prone to the alternation in landscapes and water systems, resulting in the formation of current phylogeographical structures. Recent phylogeographic studies on two gudgeon species have congruently revealed similar scenarios, in which the significant genetic differences between the coastal river populations and Yangtze River populations were attributed to the long-term isolation between these river drainages as a result of the orogenic events in southeastern China (Yang et al, 2022;Li M. et al, 2023). These findings, along with ours, emphasized the important role of the low mountains and hills in structuring the phylogeographic patterns of small freshwater fishes in southeastern China.…”
Section: Geological Events Drove the Early Diversificationsupporting
confidence: 80%
See 1 more Smart Citation
“…As a small resident stream fish, the pale chub might be prone to the alternation in landscapes and water systems, resulting in the formation of current phylogeographical structures. Recent phylogeographic studies on two gudgeon species have congruently revealed similar scenarios, in which the significant genetic differences between the coastal river populations and Yangtze River populations were attributed to the long-term isolation between these river drainages as a result of the orogenic events in southeastern China (Yang et al, 2022;Li M. et al, 2023). These findings, along with ours, emphasized the important role of the low mountains and hills in structuring the phylogeographic patterns of small freshwater fishes in southeastern China.…”
Section: Geological Events Drove the Early Diversificationsupporting
confidence: 80%
“…Our study found that several coastal river populations (population 13, FD; population 23, Bs; population 24, ZP; population 25, HA) exhibited higher nucleotide diversity than other populations due to the admixture of two major lineages (Figure 1A), while the remaining populations had a single lineage. Some previous studies focusing on both animals (e.g., Zhao et al, 2008;Li M. et al, 2023) and plants (e.g., Nettel et al, 2008;Havrdová et al, 2015) have attributed the elevated nucleotide diversity to a result of secondary contact. In our case, population 13 (FD) was originated from a small coastal stream (Tongshanxi River).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Two temporal patterns of rapid population expansion prior to the last glacial maximum (LGM, 0.026-0.019 Ma) and after the LGM detected in different lineages of G. rivuloides have also been reported in other East Asia freshwater fishes [10,80,81]. However, previous phylogeographic research of freshwater fishes in East Asia offers the strongest evidence of the pattern of rapid population expansion prior to LGM (e.g., [18,21,23,46,49]).…”
Section: Genetic Structure and Historical Demographymentioning
confidence: 93%
“…In the absence of a known genus Gobio fossil, we adopted the methods of previous studies [21,49] by reconstructing the time-calibrated Bayesian phylogeny of G. rivuloides and its close relatives to gain a secondary calibration point in BEAST v2.6.7 [56]. The Leuciscide were selected as the outgroup taxa of the Gobionidae based on the results of previous studies using multi-loci nuclear data [57,58] or mitochondrial genome data [59].…”
Section: Phylogeny and Ancestral Area Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation